2019
DOI: 10.3390/ma12223716
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nb-Content on the Microstructures and Corrosion Properties of CrFeCoNiNbx High-Entropy Alloys

Abstract: This work studied the effect of niobium-content on the microstructures, hardness, and corrosion properties of CrFeCoNiNbx alloys. Results indicated that the microstructures of these alloys changed from granular structures (CrFeCoNi alloy) to the hypereutectic structures (CrFeCoNiNb0.2 and CrFeCoNi0.4 alloys), and then to the hypoeutectic microstructures (CrFeCoNiNb0.6 and CrFeCoNi alloys). The lattice constants of the major two phases in these alloys, fcc and Laves phases (hcp), increased with the increasing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…However, the Cr 27 Fe 24 Co 18 Ni 26 Nb 5 alloy was a dual-phased alloy, because the solid solubility of Nb in the alloy could change its composition. According to our previous studies on CrFeCoNiNb x alloys[15,18], the Nb content in the FCC phase of CrFeCoNiNb x alloys changes with the Nb content(x), as shown in Figure2. The Nb content in the FCC phase of the alloys increases with the Nb content, becoming almost saturated at x = 0.6.…”
mentioning
confidence: 76%
“…However, the Cr 27 Fe 24 Co 18 Ni 26 Nb 5 alloy was a dual-phased alloy, because the solid solubility of Nb in the alloy could change its composition. According to our previous studies on CrFeCoNiNb x alloys[15,18], the Nb content in the FCC phase of CrFeCoNiNb x alloys changes with the Nb content(x), as shown in Figure2. The Nb content in the FCC phase of the alloys increases with the Nb content, becoming almost saturated at x = 0.6.…”
mentioning
confidence: 76%
“…Particularly, the added 10 wt.% WC clearly enhanced the comprehensive corrosion resistance and easy passivation of the alloy [8]. Our previous studies showed that the CrFeCoNi(Nb,Mo) alloys [9] and CrFeCoNiNb x alloys [10] all had better corrosion resistance than commercial 304 stainless steel. These alloys indicated that the CrFeCoNi-based alloys had a potential to develop alloys with good corrosion resistance.…”
Section: Introductionmentioning
confidence: 85%
“…The non-equimolar Cr 19 Fe 22 Co 21 Ni 25 Mo 13 alloy possessed better corrosion resistance compared with 304 stainless steel in both deaerated 1 M HNO 3 and 1 M HCl solutions [ 17 ]. The corrosion resistance of FeCuNbSiB and CrFeCoNiNb x alloys can be improved by adding niobium [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%